2020
DOI: 10.3892/ol.2020.11684
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of active ERK in cancer: A potential target for enhancing radiosensitivity (Review)

Abstract: Ionizing radiation (IR) is an important cancer treatment approach. However, radioresistance eventually occurs, resulting in poor outcomes in patients with cancer. Radioresistance is associated with multiple signaling pathways, particularly pro-survival signaling pathways. The extracellular signal-regulated kinase 1/2 (ERK1/2) cascade is an important signaling pathway that initiates several cellular processes and is regulated by various stimuli, including IR. Although numerous studies have demonstrated the pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 114 publications
3
25
0
Order By: Relevance
“…First, our results recognized the reversal of RT-induced ERK phosphorylation when we selectively blocked the RT-induced MMP9. We and others have shown that RT induces ERK phosphorylation in surviving tumor cells (Aravindan et al 2013c;Ala et al 2020;Lu et al 2020). Likewise, regulation of ERK phosphorylation by MMP9 in the presence and/or absence of RT has been previously documented (Bhoopathi et al 2008;Kunigal et al 2008;Gogineni et al 2009).…”
Section: Discussionsupporting
confidence: 59%
“…First, our results recognized the reversal of RT-induced ERK phosphorylation when we selectively blocked the RT-induced MMP9. We and others have shown that RT induces ERK phosphorylation in surviving tumor cells (Aravindan et al 2013c;Ala et al 2020;Lu et al 2020). Likewise, regulation of ERK phosphorylation by MMP9 in the presence and/or absence of RT has been previously documented (Bhoopathi et al 2008;Kunigal et al 2008;Gogineni et al 2009).…”
Section: Discussionsupporting
confidence: 59%
“…Activation of this chemokine signaling pathway leads to activation of the pERK pathway, that plays a significant role in regulating cancer progression. It is important to note that ERK activation can play dual roles in cancer in a context-dependent manner by either activating pro-survival or apoptotic mechanisms [40]. Clinical studies also indicate a variable association between ERK activation and tumor progression and could correlate with either an oncogenic or a tumor-suppressing role [41].…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated MAPK signaling is implicated in the progression of a wide range of cancers and occurs via multiple mechanisms, including abnormal expression of RTKs and/or genetic mutations that trigger the activation of RTKs and, thus, of downstream signaling molecules in the absence of appropriate stimuli [ 71 ]. Numerous studies focus on the dual role of MAPK signaling pathways that can mediate cell transformation, as well as apoptosis, such as the ERK and JNK signaling pathways [ 72 , 73 , 74 ]. However, there is still much to be deciphered in terms of regulation and mode of action in both preclinical and clinical research.…”
Section: Circrna-mediated Regulation Of Major Signaling Pathwaysmentioning
confidence: 99%